Investigation of thermal conductivity of multi walled carbon nanotube dispersed in hydrogenated oil based drilling fluids - Chai, Y.H. (Elsevier Ltd, 2016)
Thermal conductivity properties of non-polar hydrogenated based-oil dispersed with multi-walled carbon nanotubes (MWCNT) are investigated. The dispersion of MWCNT are carried out via two-step methods that utilizes the combination of hydrodynamic cavitation and ultrasonication dispersion at weight concentration of 25Â ppm, 50Â ppm and 100Â ppm respectively. MWCNT structure and chemical compound was analyzed using TEM imaging and FTIR analysis. The thermal conductivity of MWCNT-hydrogenated oil shows 9.8 enhancement at 100Â ppm concentration as compared to 7.2 and 4.5 enhancement at 50Â ppm and 25Â ppm respectively. Various conventional thermal conductivity models were compared with experimental data obtained, of which Nan et al. model yields the closest result approximations at 25Â ppm while other models underpredicted the thermal conductivity of MWCNT-hydrogenated oil nanofluid. Â© 2016 Elsevier Ltd